Dynamic mechanical analysis of polyethylene terephthalate/hydroxyapatite biocomposites for tissue engineering applications - Sughanthy S.A.P.; Ansari M.N.M.; Atiqah A. (Elsevier Editora Ltda, 2023)
Biocompatibility; Biomaterials; Biomechanics; Composite materials; Dichloromethane; Dynamics; Functional polymers; Hydroxyapatite; Morphology; Polyethylene terephthalates; Polyethylenes; Scaffolds (biology); Scanning electron microscopy; Tissue; Tissue engineering; Dynamic mechanical analysis (DMA); Engineering polymers; Nano bio composites; Nanofibrous scaffolds; Polyethylene terephthalates (PET); Synthetic biomaterials; Thermomechanical properties; Tissue engineering applications; Plastic bottles